Integrated multispectral imaging, germination phenotype, and transcriptomic analysis provide insights into seed vigor responsive mechanisms in quinoa under artificial accelerated aging - Yan, Huifang; Zhang, Zhao; Lv, Yanzhen; Nie, Yuting (Frontiers in Plant Science, 2024)
Seed vigor is an important trait closely related to improved seed quality and long-term germplasm conservation, and it gradually decreases during storage, which has become a major concern for agriculture. However, the underlying regulatory mechanisms of seed vigor loss in terms of genes remain largely unknown in quinoa. Here, two cultivars of quinoa seeds with different storage performance, Longli No.4 (L4) and Longli No.1 (L1), were subjected to transcriptome sequencing to decipher the pathways and genes possibly related to vigor loss under artificial aging. Multispectral imaging features and germination phenotypes showed significantly less seed vigor loss in L1 than in L4, indicating L1 seeds having stronger aging resistance and storability. Totally, 272 and 75 differentially expressed genes (DEGs) were, respectively, identified in L4 and L1 during aging. Transcriptomic analysis further revealed the differences in metabolic pathways, especially, flavonoid biosynthesis, TCA cycle, and terpenoid backbone biosynthesis were significantly enriched in L4 seeds, while carbon metabolism in L1 seeds, which involved key genes such as CHS, CHI, AACT, ENO1, IDH, NADP-ME, and HAO2L. It indicated that the adverse effects on flavonoids and terpenoids induced by aging might be the significant reasons for more vigor loss in storage sensitive seeds, whereas storage tolerant seeds had a stronger ability to maintain carbon metabolism and energy supply. These findings elucidated the underlying molecular mechanism of seed vigor loss in quinoa, which also provided novel insights into improving seed vigor through modern molecular breeding strategies.